THE EFFECTIVENESS OF THE DRUG KENTRON IN SEVERE FORMS OF NEUROPATHY OF THE FACIAL NERVE - Rakhmatova, D.I. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: Assessment of the effectiveness of the drug Kentron in severe forms of facial neuropathy. Material and methods: 52 (100%) patients with severe degrees of IOL were included in the study. Of these, 32 (61.5%) received standard therapy with the addition of a drug with the metabolic effect of Kentron 5.0 ml IM once a day for 10 days (main group), 20 (38.4%) patients of the comparison group received standard therapy, including angioprotectors, anti-inflammatory drugs that improve blood rheology, physiotherapy and physiotherapy. Results: Kentron improves conduction along the motor fibers of the facial nerve, affects nerve fibers modified by the pathological process, which is also confirmed by the clinical picture. The use of Kentron in the complex treatment of facial neuropathy can improve results, achieve a pronounced decrease in paresis of the facial muscles, and in the acute stage, complete restoration of the movements of the facial muscles in a short time. When appointing Kentron, we did not observe the development of contractures. Conclusions: Kentron is an effective drug for the treatment of facial neuropathy, regardless of the duration of the disease and the start of treatment. The effectiveness of the drug increased with early administration and was determined by a decrease in the time of full recovery to 7-10 days.